Neutrophil Gelatinase-Associated Lipocalin Levels in Early and Late Onset Preeclampsia - Guralp, Onur; Tuten, Nevin; Oncul, Mahmut; Acikgoz, Serdar A; Ekmekci, Hakan; Tuten, Abdullah (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: To evaluate the serum neutrophil gelatinase-associated lipocalin levels in pregnant women with and without preeclampsia, early-onset preeclampsia and late-onset preeclampsia, preeclampsia with and without severe features, and investigate the correlation with the neonatal outcomes. Study Design: A total of 79 pregnant women, 27 with uncomplicated pregnancies, 30 with early-onset preeclampsia, and 22 with late-onset preeclampsia were evaluated in a cross-sectional study. Neutrophil gelatinase-associated lipocalin was measured with a colorimetric Sandwich-ELISA method. Age; body mass index; systolic and diastolic blood pressure; umbilical-artery Doppler results; serum urea, bilirubin, uric acid, AST, ALT; 24-hour protein test; birth-weight; and Apgar-scores were recorded. Results: Serum neutrophil gelatinase-associated lipocalin levels were significantly higher in women with preeclampsia compared to those without preeclampsia (p<0.001); in women with early-onset preeclampsia compared to those with late-onset preeclampsia (p<0.001); and in women with late-onset preeclampsia compared to those without preeclampsia (p=0.028). Mean serum neutrophil gelatinase-associated lipocalin levels were comparable in women with preeclampsia with and without severe features (p=0.076). The correlation analysis showed that neutrophil gelatinase-associated lipocalin was not affected by age or body mass index. Neutrophil gelatinase-associated lipocalin had a positive correlation with systolic and diastolic blood pressure and the umbilical-artery PI and RI. Serum neutrophil gelatinase-associated lipocalin had a positive correlation with serum urea (r=0.416, p=0.031) however had no significant correlation with birth-weight, Apgar-scores, uric acid and amount of proteinuria in women with preeclampsia. Conclusion: Serum neutrophil gelatinase-associated lipocalin levels were significantly higher in women with preeclampsia compared to those without preeclampsia; in women with early-onset preeclampsia compared to those with late-onset preeclampsia, and in women with late-onset preeclampsia compared to women without preeclampsia. Mean serum neutrophil gelatinase-associated lipocalin levels were comparable in women with preeclampsia with and without severe features.